Phthiria notiosa sp. nov., a new bombyliid species of the tribe Phthiriini (Diptera, Bombyliidae, Phthiriinae) from Kerman province in the south of Iran - Moghbeli, Sajjad; Gharali, Babak; Fekrat, Lida (Zootaxa, 2021)
A new species Phthiria notiosa Gharali, Mogbeli & Fekrat sp. nov. is described from the southern Iran and its diagnostic features are photographed. The new species belongs to the group of Phthiria species having the dorsal prong of the first flagellomere short. Phthiria notiosa sp. nov. is morphologically similar to Ph. vagans but it is easily distinguished from that widely distributed species in Iran by the completely black scutellum and different genitalic features.